Age‐related alterations in immune responses to West Nile virus infection. (17th October 2016) - Montgomery, R. R.
Summary: West Nile virus (WNV) is the most important causative agent of viral encephalitis worldwide and an important public health concern in the United States due to its high prevalence, severe disease, and the absence of effective treatments. Infection with WNV is mainly asymptomatic, but some individuals develop severe, possibly fatal, neurological disease. Individual host factors play a role in susceptibility to WNV infection, including genetic polymorphisms in key anti‐viral immune genes, but age is the most well‐defined risk factor for susceptibility to severe disease. Ageing is associated with distinct changes in immune cells and a decline in immune function leading to increased susceptibility to infection and reduced responses to vaccination. WNV is detected by pathogen recognition receptors including Toll‐like receptors (TLRs), which show reduced expression and function in ageing. Neutrophils, monocyte/macrophages and dendritic cells, which first recognize and respond to infection, show age‐related impairment of many functions relevant to anti‐viral responses. Natural killer cells control many viral infections and show age‐related changes in phenotype and functional responses. A role for the regulatory receptors Mertk and Axl in blood–brain barrier permeability and in facilitating viral uptake through phospholipid binding may be relevant for susceptibility to WNV, and age‐related up‐regulation of Axl has been noted previously in human dendritic cells. Understanding the specific immune parameters and mechanisms that influence susceptibility to symptomatic WNV may lead to a better understanding of increased susceptibility in elderly individuals and identify potential avenues for therapeutic approaches: an especially relevant goal, as the world's populating is ageing. Abstract : West Nile virus (WNV) is the most important causative agent of viral encephalitis worldwide and is an important public health concern in the USA due to its high prevalence, severe disease, and the absence of effective treatments. Individual host factors play a role in susceptibility to WNV infection, but age is the most well‐defined risk factor for susceptibility to severe disease. Understanding the specific immune parameters and mechanisms that influence susceptibility to symptomatic WNV may lead to a better understanding of increased susceptibility in elderly individuals.